The cancer-fighting kitchen, second edition : nourishing, big-flavor recipes for cancer treatment and recovery - Katz, Rebecca; Edelson, Mat (Ten Speed Press, 2017)
"This new and revised edition of the IACP award-winning cookbook brings the healing power of delicious, nutritious foods to those whose hearts and bodies crave a revitalizing meal, through 150 new and updated recipes. Featuring science-based, nutrient-rich recipes that are easy to prepare and designed to give patients a much-needed boost by stimulating appetite and addressing treatment side effects including fatigue, nausea, dehydration, mouth and throat soreness, tastebud changes, and weight loss. A step-by-step guide helps patients nutritionally prepare for all phases of treatment, and a full nutritional analysis accompanies each recipe. This remarkable resource teaches patients and caregivers how to use readily available powerhouse ingredients to build a symptom- and cancer-fighting culinary toolkit. Blending fantastic taste and meticulous science, these recipes for soups, vegetable dishes, proteins, and sweet and savory snacks are rich in the nutrients, minerals, and phytochemicals that help patientsthrive during treatment. This second edition also includes a dozen new recipes--many of which are simpler and less complicated, for cancer patients to prepare on their low days--as well as a list of cancer-fighting foods that can be incorporated into everyday life without stepping behind the stove. Rebecca has also revised the text with the most up-to-date scientific research and includes a section on how friends and family can build a culinary support team"--